GENDERED SOCIAL INDICATORS AND GROUNDED THEORY. - Austen, Siobhan; Jefferson, Therese; Thein, Vicki (Feminist Economics, 2003)
This article outlines a pilot program undertaken to assess the advantages and disadvantages of including significant elements of grounded theory in research measuring women's progress. This pilot program, carried out in Western Australia, aimed at broadening the range of data collection and analysis methods in the field of gendered social and economic indicators. It featured ten affinity group discussions with sixty-two women and six men on the issue of women's progress in the region. The results have implications for future research on women's wellbeing.